INVESTIGASI NON DESTRUKTIF DENGAN PROFOMETER - Hariwarsianto Hariwarsianto; Moga Narayudha (TEKNIK, 2008)
Concrete structures obtain their strength and load carrying capacity from the compatibility of concrete’scompression capacity and steel’s tensile strength. When a structure is in service, the concretecompression strength can easily be measured with all kinds of equipment, both non destructive, semi anddestructive.While the methods of analysis concrete in existing buildings is fairly straight forward and widely known,the determination of reinforcement embedded in the concrete is a more complicated matter. Beside thesteel’s tensile strength, the bar’s configuration is very important, since the load carrying capacity isdepending on it. One destructive method is to un-mantle the bars and observes and measures the sizesand configuration manually. This will involve not only skilled labor but is time consuming and costly.One technology to overcome these difficulties is the use of rebar locators. The measuring method is basedon the eddy-current principle with pulse-induction. Important data as concrete cover, bar configurationand bar size can be obtained. This paper will discuss the principles of rebar locators, and will include acase study where structural capacity is calculated based on non destructive testing